Antioxidant Activity of Methanol Extract of the Purun Tikus (Eleocharis dulcis) Leaves - Kholifatu Rosyidah; Taufiqur Rohman; Ridhana Fitriani (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2018)
Purun tikus (Eleocharis dulcis) is a kind of swamp plant, can be found in open water areas, both in swamps and rice fields. Purun tikus is an indicator vegetation of acidic sulfate soil. Chemically, plants that able to adapt to special or extreme conditions, usually produce a compound that are unique and have unique bioactivity as well. This paper reports a phytochemical screening of Purun tikus methanol extract and its antioxidant activity. The results showed that the methanol extract of Purun tikus leaves contained phenolic compounds, flavonoids, tannins and terpenoids. By using DPPH method as an antioxidant test, the methanol extract of purun tikus leaves showed a strong activity, with IC50 value was 58.58 ppm while vitamin C had an IC50 value of 4.50 ppm.